Numerical simulation of the equatorial plasma bubble: the effect of seeding by the vertical winds and random background noise perturbations - Zhu, Yunzhou; Tang, Qiong; Xu, Tong; Liu, Yi; Zhou, Chen; Deng, Zhongxin; Zhang, Yuqiang; Zhao, Zhengyu; Wei, Fengsi; Xu, Bin; Sun, Shuji (Frontiers in Astronomy and Space Sciences, 2023)
A wide variety of small-amplitude waves widely exist in the ionosphere and have significant effects on the evolution of equatorial plasma bubbles. In this paper, we simulated equatorial plasma bubbles (EPB) seeded by vertical neutral wind perturbations with wavelengths of 125 km and 250 km, and compared the morphology characteristics of plasma bubble structures with those under random noise perturbations in the background density. The numerical results showed that both vertical winds and random background noise perturbations can contribute to the growth of plasma bubbles, and the perturbations under additional random background noise can promote the growth of the plasma bubble structures faster. Additionally, several processes of the nonlinear behavior of bifurcated EPB structures, including bifurcation, pinching, and small-scale turbulent structures, were successfully obtained. Our simulation captured supersonic flows within the low-density plasma structures characterized by vertical velocities of about 1.5 km/s, which is consistent with experimental studies found in the literature.